Enteric Glia: S100, GFAP, and Beyond - Grundmann, David; Loris, Eva; Maas‐Omlor, Silke; Huang, Wenhui; Scheller, Anja; Kirchhoff, Frank; Schäfer, Karl Herbert (The anatomical record, 2019)
Since several years, the enteric nervous system (ENS) is getting more and more in the focus of gastrointestinal research. While the main interest was credited for years to the enteric neurons and their functional properties, less attention has been paid on the enteric glial cells (EGCs). Although the similarity of EGCs to central nervous system (CNS) astrocytes has been demonstrated a long time ago, EGCs were investigated in more detail only recently. Similar to the CNS, there is not “the” EGC, but also a broad range of diversity. Based on morphology and protein expression, such as glial fibrillary acidic protein (GFAP), S100, or Proteolipid-protein-1 (PLP1), several distinct glial types can be differentiated. Their heterogeneity in morphology, localization, and transcription as well as interaction with surrounding cells indicate versatile functional properties of these cells for gut function in health and disease. Although NG2 is found in a subset of CNS glial cells, it did not colocalize with the glial marker S100 or GFAP in the ENS. Instead, it in part colocalize with PDGFRα, as it does in the CNS, which do stain fibroblast-like cells in the gastrointestinal tract. Moreover, there seem to be species dependent differences. While GFAP is always found in the rodent ENS, this is completely different for the human gut. Only the compromised human ENS shows a significant amount of GFAP-positive glial cells. So, in general we can conclude that the EGC population is species specific and as complex as CNS glia. Anat Rec, 302:1333-1344, 2019. © 2019 Wiley Periodicals, Inc.